Blood-feeding patterns of Anopheles mosquitoes in a malaria-endemic area of Bangladesh - Bashar Kabirul; Tuno Nobuko; Ahmed Touhid; Howlader Abdul (Parasites & Vectors, 2012)
Abstract Background Blood-feeding patterns of mosquitoes are crucial for incriminating malaria vectors. However, little information is available on the host preferences of Anopheles mosquitoes in Bangladesh. Therefore, the objective of the present study was to determine the hematophagic tendencies of the anophelines inhabiting a malaria-endemic area of Bangladesh. Methods Adult Anopheles mosquitoes were collected using light traps (LTs), pyrethrum spray (PS), and human bait (HB) from a malaria-endemic village (Kumari, Bandarban, Bangladesh) during the peak months of malaria transmission (August-September). Enzyme-linked immunosorbent assay (ELISA) and polymerase chain reaction (PCR) were performed to identify the host blood meals of Anopheles mosquitoes. Results In total, 2456 female anopheline mosquitoes representing 21 species were collected from the study area. Anopheles vagus Doenitz (35.71%) was the dominant species followed by An. philippinensis Ludlow (26.67%) and An. minimus s.l. Theobald (5.78%). All species were collected by LTs set indoors (n = 1094), 19 species were from outdoors (n = 784), whereas, six by PS (n = 549) and four species by HB (n = 29). Anopheline species composition significantly differed between every possible combination of the three collection methods (χ2 test, P < 0.001). Host blood meals were successfully detected from 1318 (53.66%) Anopheles samples belonging to 17 species. Values of the human blood index (HBI) of anophelines collected from indoors and outdoors were 6.96% and 11.73%, respectively. The highest values of HBI were found in An. baimai Baimaii (80%), followed by An. minimus s.l. (43.64%) and An. annularis Van den Wulp (37.50%). Anopheles baimai (Bi = 0.63) and An. minimus s.l. (Bi = 0.24) showed strong relative preferences (Bi) for humans among all hosts (human, bovine, goats/sheep, and others). Anopheles annularis, An. maculatus s.l. Theobald, and An. pallidus Theobald exhibited opportunistic blood-feeding behavior, in that they fed on either humans or animals, depending on whichever was accessible. The remaining 12 species preferred bovines as hosts. Conclusions The observed high anthropophilic nature of An. baimai, An. minimus s.l., and An. annularis revealed these species to be important malaria vectors in hilly areas of Bangladesh. Higher values of HBI in outdoor-resting mosquitoes indicated that indoor collection alone is not adequate for evaluating malaria transmission in the area.